Multiple sclerosis and suicide - Feinstein, Anthony; Pavisian, Bennis (Multiple sclerosis, 2017)
Mortality rates are elevated in people with multiple sclerosis (MS) relative to the general population. There is, however, some uncertainty whether suicide contributes to this. Epidemiological data suggest that the standardized mortality ratio (SMR) for suicide in MS is approximately twice that of the general population with younger males in the first few years following diagnosis most at risk. Rates of suicidal intent, a potential harbinger of more self-destructive behavior, are also elevated, but the frequency with which intent is followed by suicide is not known. Depression, severity of depression, social isolation, and alcohol abuse are associated with thoughts of suicide. The variables linked with suicide and suicidal intent are therefore well defined and should be readily available from routine clinical inquiry. While vigilance on the part of clinicians is required, particularly in the context of high-risk patients, it is also recognized that prevention is dependent on full disclosure of intent.